2013
DOI: 10.1155/2013/407839
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Resveratrol against Arsenic Trioxide-Induced Cardiotoxicity

Abstract: Arsenic trioxide (As2O3) shows substantial anticancer activity in patients with acute promyelocytic leukemia (APL). Unfortunately, limiting the application of this effective agent to APL patients is severe cardiotoxicity. Resveratrol, the natural food-derived polyphenolic compound, is well known for its antioxidant properties and protects the cardiovascular system. But the potential role of resveratrol against As2O3 in heart via nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Resveratrol has also been shown to protect against arsenic trioxide-induced cardiotoxicity in mice and rats [276,277]. The protection against cisplatin and arsenic trioxide-induced cardiotoxicity has been attributed to the increase in the endogenous anti-oxidant enzymes activity namely, SOD, catalase, and glutathione peroxidase [270,277], in addition to activation of the anti-oxidant NRF2-heme oxygenase-1 pathway [276], suggesting the importance of the anti-oxidant properties of resveratrol in these models as well. Recently, an in vitro study has reported that resveratrol protects against sunitinib-induced hypertrophy in H9c2 cells [278].…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Resveratrol has also been shown to protect against arsenic trioxide-induced cardiotoxicity in mice and rats [276,277]. The protection against cisplatin and arsenic trioxide-induced cardiotoxicity has been attributed to the increase in the endogenous anti-oxidant enzymes activity namely, SOD, catalase, and glutathione peroxidase [270,277], in addition to activation of the anti-oxidant NRF2-heme oxygenase-1 pathway [276], suggesting the importance of the anti-oxidant properties of resveratrol in these models as well. Recently, an in vitro study has reported that resveratrol protects against sunitinib-induced hypertrophy in H9c2 cells [278].…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%
“…Wang J et al have shown that resveratrol alleviated cisplatin-induced myocardial damage in a dose-dependent manner demonstrated by an improvement in histological appearance of the myocardium and normalization of markers of myocardial damage such as creatine kinase (CK) and lactate dehydrogenase (LDH) [270]. Resveratrol has also been shown to protect against arsenic trioxide-induced cardiotoxicity in mice and rats [276,277]. The protection against cisplatin and arsenic trioxide-induced cardiotoxicity has been attributed to the increase in the endogenous anti-oxidant enzymes activity namely, SOD, catalase, and glutathione peroxidase [270,277], in addition to activation of the anti-oxidant NRF2-heme oxygenase-1 pathway [276], suggesting the importance of the anti-oxidant properties of resveratrol in these models as well.…”
Section: Chemotherapy-induced Cardiotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, antioxidants such as resveratrol also possess similar effects as they were shown to prevent the down-regulation of Nrf2 and HO-1 in rats administered with ATO [125]. Resveratrol also decreased ROS generation and oxidative DNA damage.…”
Section: Cellular Signalingmentioning
confidence: 88%
“…Notably, we present for the first time a DNA microarray and proteomics analysis of the molecular signaling of arsenic trioxide‐induced apoptotic cell death in mesenchymal stem cells. Previous results ever showed that arsenic trioxide is able to provoke apoptotic death through DNA damage on cardiotoxicity (Zhang et al, ), A549 cells (Kryeziu et al, ), osteosarcoma (Nakamura et al, ), PLHC‐1 fish cells (Selvaraj et al, ), HL‐60 cells (Yedjou and Tchounwou, ; Yoda et al, ), melanoma (Balaz and Sedlak, ), and human HaCaT cells keratinocyte (Udensi et al, ). Our results indicated that arsenic trioxide is able to increase cell population of sub‐G1 phase in HUMSC and HMSC‐bm.…”
Section: Discussionmentioning
confidence: 99%